2014
DOI: 10.1002/eji.201344183
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures and transcriptional regulatory networks of human immature decidual NK and mature peripheral NK cells

Abstract: Many differences exist between human immature and mature natural killer (NK) cells, but their respective molecular signatures and transcriptional regulators are relatively unknown. To gain new insights into the diversity and developmental regulation of human NK cells, we used data from high-resolution microarrays with independent verification to describe a comprehensive comparative analysis between immature decidual NK (idNK) cells with a Eur. J. Immunol. 2014. 44: 2771-2784 activity [6,7]. Our previous work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
5
31
0
Order By: Relevance
“…In addition, current knowledge of the molecular mechanisms that govern the onset and maintenance of specific human NK cell phenotypes is still incomplete. Our previous work indicated that pNK and dNK cells differ in their patterns of gene and microRNA expression [12, 13]. The present study extends this comparison to long noncoding RNAs among different human NK cell populations.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, current knowledge of the molecular mechanisms that govern the onset and maintenance of specific human NK cell phenotypes is still incomplete. Our previous work indicated that pNK and dNK cells differ in their patterns of gene and microRNA expression [12, 13]. The present study extends this comparison to long noncoding RNAs among different human NK cell populations.…”
Section: Discussionsupporting
confidence: 72%
“…However, the in vivo situation is much more difficult to examine due to existing complex molecular networks and cellular interactions. 40 For example, we did not find IFN-c changes at the protein level when dNK cells were cocultured with HTR-8 trophoblast cells, although N. Sotnikova et al reported that trophoblast cells increased the mRNA expression of IFN-c by dNK cells. 41 These results suggest that dNK cells have tightly controlled thresholds for the transcription and translation of reactive cytokines.…”
Section: Discussionmentioning
confidence: 72%
“…10 In comparison with peripheral NK cells, dNK represent a specified NK population with limited cytolytic activity. 11,12 During early gestational stage, dNK cells express NKp46 (CD335/NCR1), NKp44 (CD336/NCR2), and NKp30 (CD337/NCR3), activating receptors NKG2D (CD314) and NKp80 to regulate their immune reactions and angiogenesis ability. 13,14 In addition to intra-cellular signaling pathways, dNK cell function can be modulated by these receptors through inter-cellular communication.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are consistent with one report [10] of immunostaining for NK cells within the human CL, and provides evidence of their dynamics during the primate luteal lifespan. Primate NK cells are divided into two subtypes: immature (5% of total population) and mature (95% of population) NK cells [42,43]. The immature subtype secretes more cytokines than mature NK cells, whereas mature NK cells mainly function to lyse target cells via an MHC-independent mechanism (as reviewed by Caligiuri [43]).…”
Section: Discussionmentioning
confidence: 99%